1992
DOI: 10.1093/nar/20.17.4649
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of human and bovine homologs of SNF2/SWI2: a global activator of transcription in yeastS.cerevisiae

Abstract: We performed positional cloning of genes carried on yeast artificial chromosomes that span a human translocation breakpoint associated with a human disease and isolated by chance human and bovine genes with strong homology to the S. cerevisiae genes, SNF2/SWI2 and STH1, and the D. melanogaster gene brahma. We report here sequence analysis, expression data, and functional studies for this human SNF2-like gene (hSNF2L) and its bovine homolog (bovSNF2L). Despite strong homology at the amino acid level, hSNF2L is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 21 publications
0
66
0
2
Order By: Relevance
“…36 We found that the expression of Smarca1 mRNA and protein peaked at passages 8-9, followed by a decline after p53LOH was attained in the majority of the population (Figures 7c-e). No change in the expression patterns of other major chromatin remodelers, 36 such as Smarca2, Smarca4 and Smarca5, was observed (Supplementary Figure 9). This indicates a unique correlation between Smarca1 expression and p53LOH.…”
Section: Resultsmentioning
confidence: 77%
“…36 We found that the expression of Smarca1 mRNA and protein peaked at passages 8-9, followed by a decline after p53LOH was attained in the majority of the population (Figures 7c-e). No change in the expression patterns of other major chromatin remodelers, 36 such as Smarca2, Smarca4 and Smarca5, was observed (Supplementary Figure 9). This indicates a unique correlation between Smarca1 expression and p53LOH.…”
Section: Resultsmentioning
confidence: 77%
“…Furthermore, chromatin structure on the SUC2 promoter is altered in snJ2 and sniS mutants (38). Finally, homologs of SWI2/SNF2 have been identified in yeast (16,17), Drosophila (39,40), mouse (41), and humans (42,43), and the protein encoded by the Drosophila brm gene appears to affect the transcription of several genes by assisting in the remodeling of chromatin structure (44). Thus, complexes analogous to the yeast SWP complex may help in general to mediate the transition from the repressed to the derepressed state of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are ered to a synthetic DNA-binding domain, hSNF2L is unable to important regulatory factors in several pathways of gene expresactivate the transcription of a reporter gene or to complement sion. Saccharomyces cerevisiae Snf2 has been shown to form a snf2 mutations in S. cerevisiae [15]. Conversely, hSNF2L and multiprotein complex, Snf/Swi, together with Swi1, Swi3, Snf5…”
mentioning
confidence: 99%